A new class of integral-multipoint boundary value problems for nonlinear Hadamard fractional differential equations on a semiinfinite domain - Nyamoradi, Nemat; Ahmad, Bashir; Ntouyas, Sotiris K. (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we introduce and investigate a new class of Hadamard fractional differential equation with integral-multipoint boundary conditions on a positive semiinfinite domain. We use the contraction mapping principle and the fixed point index theorem, respectively, to prove the uniqueness and the existence of at least two positive solutions to the given problem. Our results are new and enrich the literature on Hadamard-type fractional differential equations on unbounded domains. Some examples illustrating the main results are presented.
Keywords: Hadamard fractional derivative; contraction mapping principle; fixed point index theorem; positive solution; unbounded domain